Methodology for the identification and prioritization of economic activities that contribute to the innovation strategy for smart specialization: Case of the Arequipa Region - Mauricio Meza (2019)
The study presents a methodological proposal for the identification and prioritization of economic activities that contribute to the innovation strategy for smart specialization in the Arequipa region, considers both quantitative and qualitative data, based on statistical information and qualifications granted by the actors representing the quadruple propeller (academy, government, business and civil society), of the Regional Innovation System (SRI), respectively. These data defined in a framework of critical factors, such as the potential for economic growth, competitiveness, connectivity and cluster, will allow determining the prioritization of economic activities in the region. The result of the application of the methodology prioritizes the mining activity; agriculture-agribusiness activity; and manufacturing activity: textile of South American camelids in the region of Arequipa, Peru.